Sharia Board Characteristics, Macroeconomic Factors, and Non-performing Financing of Indonesian Islamic banks - Mai, Muhamad Umar; Kristianingsih, Kristianingsih; Dahtiah, Neneng (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2023)
This study examines the impact of Islamic board characteristics (SB) and macroeconomic factors on the Non-performing financing (NPF) of Islamic commercial banks (ICB). The sample of this study consisted of 14 ICBs in Indonesia from 2010 to 2021. In this study, data estimation used a one-step GMM System model. SB features such as SB Size and SB Woman were found to have a detrimental impact on NPF. GDP per capita, for example, negatively affects NPF, while inflation has a positive impact. However, this study could not show the impact of SB characteristics such as expertise and proximity of SB to NPF. The study also found that macroeconomic factors such as annual open unemployment and interest rates showed an insignificant negative influence on NFP. The findings of this study help regulators, investors, and management of Islamic banks better understand the impact of SB characteristics and macroeconomic factors on Non-performing financing (NPF) of Islamic banks, especially in the context of ICB in Indonesia. In addition, it is expected to inspire similar research in the future.